2017
DOI: 10.1111/jcpp.12828
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Early intervention for infants and young children with, or at‐risk of, autism spectrum disorder: a systematic review

Abstract: There has been a substantial increase in the number of RCTs evaluating early interventions in ASD. However, few studies, only 12.5% of the total, were rated as being at low risk of bias. Small sample size, unclear concealment of allocation and lack of clarity in the identification of the active ingredients in a diverse range of differently named treatment models were identified as challenges to the design, conduct and interpretation of studies. Improved co-ordination and design of studies is, therefore, requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 87 publications
5
140
0
2
Order By: Relevance
“…A third key step will be the explicit investigation of mechanism, which will allow an iterative evolution towards more refined treatments (Green, 2015;Kraemer, Wilson, Fairburn, & Agras, 2002). The first part of this review consequently builds on French and Kennedy (2018) by focusing on the (explicit or implicit) mechanisms and treatment targets within the variety of treatments tested to dateparticularly in those studies reviewed by French and Kennedy (2018) as having relatively low risk of bias. We aim through this to provide a unifying view of the current research along with an agenda for moving forward with new and refined mechanism targets.…”
Section: Trial Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A third key step will be the explicit investigation of mechanism, which will allow an iterative evolution towards more refined treatments (Green, 2015;Kraemer, Wilson, Fairburn, & Agras, 2002). The first part of this review consequently builds on French and Kennedy (2018) by focusing on the (explicit or implicit) mechanisms and treatment targets within the variety of treatments tested to dateparticularly in those studies reviewed by French and Kennedy (2018) as having relatively low risk of bias. We aim through this to provide a unifying view of the current research along with an agenda for moving forward with new and refined mechanism targets.…”
Section: Trial Methodsmentioning
confidence: 99%
“…Two recent studies in the French and Kennedy () review found treatment effects on parent ‘responsiveness’ in autism. A 12 week ‘Focused Playtime Intervention’ (FPI) that combined live modelling from therapist to parent with video‐feedback and psycho‐education was tested in a pre‐emptive study of 66 toddlers at high autism‐risk mean age 22 months (Kasari, Siller et al., ).…”
Section: Targets and Mechanisms In Psychosocial Autism Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…have drawn attention to how the heterogeneity of autism challenges our capacity to understand and evaluate trajectories and outcomes from intervention, noting that it is unlikely that all individuals with autism will benefit from the same types of approaches . Indeed, despite best research efforts, controversy remains about the most effective interventions for children with autism . In their review of early intervention research, Stahmer et al .…”
Section: How Do We Move Towards Precision Medicine For Children With mentioning
confidence: 99%
“…There is growing evidence that early intervention leads to sustained improvements and hence better outcomes and a better quality of life, but at the same time more and better (follow‐up) research is needed. The current findings on early intervention are also described as promising and encouraging …”
mentioning
confidence: 90%